2020
DOI: 10.3389/fpls.2020.00720
|View full text |Cite
|
Sign up to set email alerts
|

The Pepper MAP Kinase CaAIMK1 Positively Regulates ABA and Drought Stress Responses

Abstract: Protein phosphorylation and dephosphorylation are important mechanisms that regulate many cellular processes. Protein kinases usually function in the regulation of the stress responses by adjusting activity via phosphorylation of target proteins. Here, we isolated CaAIMK1 (Capsicum annuum ABA Induced MAP Kinase 1) from the pepper leaves that had been subjected to drought stress. CaAIMK1 transcripts were induced by drought, abscisic acid (ABA), high salinity, and H 2 O 2 ; further, the CaAIMK1-Green fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Protein phosphatases and kinases are major post-translational regulators of numerous cellular processes and signaling networks [86]. Protein kinases pathways are activated by sequential phosphorylation leading to the regulation of TFs and protective enzymes in response to several stresses, including drought [87]. A high up-regulation of phosphatase genes was reported under SWD (Table S9), particularly in CL153, suggesting the involvement of these genes in the drought response.…”
Section: Degs Involved In Phosphatases and Protein Kinases Affected By Droughtmentioning
confidence: 99%
“…Protein phosphatases and kinases are major post-translational regulators of numerous cellular processes and signaling networks [86]. Protein kinases pathways are activated by sequential phosphorylation leading to the regulation of TFs and protective enzymes in response to several stresses, including drought [87]. A high up-regulation of phosphatase genes was reported under SWD (Table S9), particularly in CL153, suggesting the involvement of these genes in the drought response.…”
Section: Degs Involved In Phosphatases and Protein Kinases Affected By Droughtmentioning
confidence: 99%
“…The protein kinases included RLKs, MAPKs, and calcium/calmodulin-dependent CDPKs. MAPK activity is inhibited and regulated by PP2C in plant growth and stress signaling pathways [64,65]. The differential expression of PKs in the study suggests that the PKs are associated with the prolonged drought and regulated in the induced drought conditions (Figure 7).…”
Section: Discussionmentioning
confidence: 83%
“…SnRK2 type kinases (SnRK2s) and receptor-like kinases (RLKs) are the most extensively studied protein kinases involved in drought stress tolerance among stress-related kinases. SnRK2s are involved in the ABA central signaling pathway and defense responses such as transcription and stomatal aperture control [65,66]. The PK families RLKs, and FLS2 are reported to trigger the immune response in plants through binding with the pathogen flagellin protein and regulated the stomatal closure induced by ABA through intermolecular interactions with BAK1, a co-receptor of flg22 [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…To isolate drought-induced MAP3 kinase, we used RNA-seq analysis and isolated eight MAP3 kinase genes from pepper plant leaves under drought stress: CA07g11510 , CA07g11520 , CA07g11530 , CA07g11540 , CA07g11550 ( Jeong et al, 2020 ), CA07g11570 , CA02g14340 , CA02g14350 , and CA02g14360 ( Figure 1A ). Domain analyses using a web-based tool (SMART) 1 showed that MAP3Ks have a kinase domain, which phosphorylates tyrosine or serine-threonine amino acid residues of a target protein.…”
Section: Resultsmentioning
confidence: 99%
“…Plants modulate cellular activities using several processes such as transcription and posttranslational modifications to survive drought stress. Phosphorylation mediated by protein kinase is one of the posttranslational modifications, which plays a critical function in abiotic stress response and ABA signaling ( Shi et al, 2018 ; Wang et al, 2018 ; Hong et al, 2020 ; Jeong et al, 2020 ). Previous studies reported that many protein kinases related to stress response were identified and functionally characterized; however, the exact process and function of these proteins remain elusive.…”
Section: Discussionmentioning
confidence: 99%